The Global Session Metric Score (GSMs): A Modified Session-Specific Exertional Index - Gardner, Hanna M.; Scheck, Andrew W.; Cone, John R.; Berry, Nathaniel T.; Wideman, Laurie (Frontiers in Sports and Active Living, 2021)
Monitoring session training load to optimize the training stress that drives athlete adaptation and subsequent performance, is fundamental to periodization and programming. Analyzing the internal load experienced by the individual in response to the external load prescribed by coaching staff is crucial to avoid overtraining and optimize training adaptation. Subjective measures provide more information regarding individual training load, as heart rate measures alone do not account for collisions, eccentric muscle actions, muscle soreness, weather conditions, or accumulated training loads which are paramount to the athlete experience. However, the current subjective metric for interpreting session training load (sRPE) is poorly shaped to the athlete’s global response to a session as a whole, often showing poorer correlations to heart rate measures during intermittent or high-intensity activity. This study introduces a new metric, the Global Session Metric Score (GSMs), which creates a symmetrical relation between the verbal descriptor and numeric values, as well as more accurate verbal descriptors for the highest level of exertion. Twenty-four D1 male college soccer field players (age: 20.5 +/- 1.42) wore GR monitors and reported GSMs for all practices and games within an entire season. Repeated measures correlations between GSMs and Barrister’s TRIMP and Edward’s TRIMP show a similar significant positive relation for the full (B-TRIMP = 0.88; E-TRIMP = 0.89), training only (B-TRIMP = 0.88; ETRIMP = 0.88), and game only (B-TRIMP = 0.85; E-TRIMP = 0.86) datasets (p<.001). The findings validate the GSMs index as a reliable means for measuring load in both training and matches during a high-intensity intermittent team sport. Future studies should investigate whether the variance between GSMs and TRIMP values can be attributed to the subjective metrics greater analysis of global session experience (i.e. muscle soreness, weather, accumulated training loads, etc.). GSMs provides coaches and clinicians a simple and cost-effective alternative to heart rate monitors, as well as a proficient measure of internal training load experienced by the individual.